MAURICE RAVEL'S MUSICAL CAREER AND CREATIVE STYLE - Xiaoyu, Li (E-Journal VFU, 2025)
Maurice Ravel (1875–1937) was a leading figure in French music, renowned for his ability to blend tradition with innovation, particularly in his orchestration techniques and formal structure. He is regarded as an Impressionist composer. His works are characterised by their rigorous structure, complex harmonies, and lavish orchestration. His masterpiece, “La Valse” demonstrates his unique conceptual approach and exceptional technical skill in musical form composition, serving as a paradigm of 20th-century musical aesthetics..
Keywords: Maurice Ravel; French music; Impressionism; orchestration; „La Valse“; musical style